EFFECT OF DIFFERENT BUNCH COVERING MATERIALS ON SHAMRAN DATE FOR ENHANCEMENT OF ECONOMICAL YIELD - M. A. Bashir; M. Ahmad; K. Shabir (Journal of Animal and Plant Sciences, 2015)
The experiment was carried out on date palm (Phoenix dactylifera L.) cv. "Shamran" at Horticultural Research Station, Bahawalpur (Pakistan) during 2009-11 with the objectives to observe the effect of different bunch covering materials to reduce the rainfall effect for enhancement of economical yield. The experiment was laidout in Randomized Complete Block Design with 5 replications (5 palms). A set of treatments consisting of 5 treatments such as bunches without covering treated as control treatment (T1), bunches covered with polythene bags (T2), glazed paper bags (T3), art paper bags (T4) and polypropylene bags (T5), was applied to tagged bunches on a single palm before the onset of monsoon rains in the month of June (leaving downside of the bags open). Other cultural practices i.e., irrigation, fertilizer applcation and pollination were applied uniformly to all experimental units. The parameters under study were Ferment fruit (%), Fruit drop (%), Benefit ratio (%) over control, Bunch weight (kg) and Cost benefit ratio. Three years data results average indicated that bunches which were covered with polythene bags resulted in minimum fermented fruit (13.4%), minimum fruit drop (11.3%), maximum benefit ratio (56.7%) over control, the heaviest bunch weight (6.7kg), the highest cost benefit ratio (1:34) with maximum profit (67%) over uncovered bunches, followed by those bunches which were covered with polypropylene bags in these parameters. However, bunches covered with either glazed paper bags or art paper bags, both remained statistically similar in effect on the parameters.
Keywords: Bunch cover; date palm; Phoenix dactylifera L.; productivity; rainfall